A global systematic review of socio-economic impact assessments of high-tide flooding - Xu, Yicheng; Sirianni, Hannah; Wade, Eric; Hoover, Fushcia-Ann; Mukherji, Anuradha; Narayan, Siddharth (Frontiers in Human Dynamics, 2025)
High-tide flooding (HTF) is an increasingly frequent and disruptive phenomenon in coastal regions worldwide, driven by rising local sea levels. Despite recent attention to the drivers of this emerging flood hazard, the scope and extent of socio-economic impacts of HTF impacts are not well understood. This study presents a global systematic review of studies that quantitatively assess the socio-economic impacts of HTF. A total of 993 peer-reviewed English-language studies published between 1985 and October 2024 were identified through Scopus and Google Scholar. Of these, 194 focus on HTF events, of which 26% address socio-economic impacts. The review shows that the vast majority of HTF impact studies, 72%, are focused on U.S. geographies with Indonesia having the second largest number of HTF impact studies (20%). In the United States, socioeconomic impacts from HTF events have been assessed in 24 cities across the Atlantic, Gulf and Pacific coasts with Norfolk, VA and Miami, FL on the Atlantic having the most number of assessments. HTF impacts affect multiple socio-economic sectors, including public infrastructure, private sectors, and environmental health. However, even among studies in the same sector, the use of different baselines, scales, and HTF event threshold definitions makes it difficult to compare HTF impacts across locations. From these findings our review identifies four points for further research on the socio-economic impacts of HTF to improve collective understanding of these emerging coastal risks.